Current Immunotherapies for Glioblastoma Multiforme - Huang, Boyuan; Li, Xuesong; Li, Yuntao; Zhang, Jin; Zong, Zhitao; Zhang, Hongbo (Frontiers in Immunology, 2021)
Glioblastoma multiforme (GBM) is the most common and aggressive malignant tumor found in the central nervous system. Currently, standard treatments in the clinic include maximal safe surgical resection, radiation, and chemotherapy and are mostly limited by low therapeutic efficiency correlated with poor prognosis. Immunotherapy, which predominantly focuses on peptide vaccines, dendritic cell vaccines, chimeric antigen receptor T cells, checkpoint inhibitor therapy, and oncolytic virotherapy, have achieved some promising results in both preclinical and clinical trials. The future of immune therapy for GBM requires an integrated effort with rational combinations of vaccine therapy, cell therapy, and radio- and chemotherapy as well as molecule therapy targeting the tumor microenvironment.